Humanitarian Intervention and Changing Labor Relations: The Long-term Consequences of the Abolition of the Slave Trade - Linden, M. Van Der (Studies in Global Social History, 2011)
The sixteen essays in this collection discuss the direct and indirect impact of the British Act for the Abolition of the Slave Trade (1807) on labor relations in the Americas, Africa and South East Asia.